Effect of vitamin D on cognitive decline: results from two ancillary studies of the VITAL randomized trial - Kang, Jae H.; Vyas, Chirag M.; Okereke, Olivia I.; Ogata, Soshiro; Albert, Michelle; Lee, I.-Min; D’Agostino, Denise; Buring, Julie E.; Cook, Nancy R.; Grodstein, Francine; Manson, JoAnn E. (Scientific Reports, 2021)
Low vitamin D levels have been associated with cognitive decline; however, few randomized trials have been conducted. In a trial, we evaluated vitamin D3 supplementation on cognitive decline. We included participants aged 60+ years (mean[SD] = 70.9[5.8] years) free of cardiovascular disease and cancer in two substudies in the VITAL 2 × 2 randomized trial of vitamin D3 (2000 IU/day of cholecalciferol) and fish oil supplements: 3424 had cognitive assessments by phone (eight neuropsychologic tests; 2.8 years follow-up) and 794 had in-person assessments (nine tests; 2.0 years follow-up). The primary, pre-specified outcome was decline over two assessments in global composite score (average z-scores of all tests); substudy-specific results were meta-analyzed. The pooled mean difference in annual rate of decline (MD) for vitamin D3 versus placebo was 0.01 (95% CI − 0.01, 0.02; p = 0.39). We observed no interaction with baseline 25-hydroxyvitamin-D levels (p-interaction = 0.84) and a significant interaction with self-reported race (p-interaction = 0.01). Among Black participants (19%), those assigned vitamin D3 versus placebo had better cognitive maintenance (MD = 0.04, 95% CI 0.01, 0.08, similar to that observed for Black participants 1.2 years apart in age). Thus, vitamin D3 (2000 IU/day cholecalciferol) supplementation was not associated with cognitive decline over 2–3 years among community-dwelling older participants but may provide modest cognitive benefits in older Black adults, although these results need confirmation. Trial registration ClinicalTrials.gov; VITAL (NCT01169259), VITAL-DEP (NCT01696435) and VITAL-Cog (NCT01669915); the date the registration for the parent trial (NCT01169259) was submitted to the registry: 7/26/2010 and the date of first patient enrollment in either of the ancillary studies for cognitive function in a subset of eligible VITAL participants: 9/14/2011.